2011
DOI: 10.1002/term.496
|View full text |Cite
|
Sign up to set email alerts
|

PGA-associated heterotopic chondrocyte cocultures: implications of nasoseptal and auricular chondrocytes in articular cartilage repair

Abstract: The availability of autologous articular chondrocytes remains a limiting issue in matrix assisted autologous chondrocyte transplantation. Non-articular heterotopic chondrocytes could be an alternative autologous cell source. The aims of this study were to establish heterotopic chondrocyte cocultures to analyze cell-cell compatibilities and to characterize the chondrogenic potential of nasoseptal chondrocytes compared to articular chondrocytes. Primary porcine and human nasoseptal and articular chondrocytes wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(8 citation statements)
references
References 33 publications
0
8
0
Order By: Relevance
“…Scaffold-based tissue engineering has proved its potential in regenerative medicine and has witnessed impressive progress as a tool for BTE. Previous studies have established the crucial role of microarchitecture and physical properties of structures in translating in vitro-engineered cell scaffold constructs into bone tissue [ 14 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…Scaffold-based tissue engineering has proved its potential in regenerative medicine and has witnessed impressive progress as a tool for BTE. Previous studies have established the crucial role of microarchitecture and physical properties of structures in translating in vitro-engineered cell scaffold constructs into bone tissue [ 14 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have demonstrated that the microarchitectures of porous scaffolds, in terms of porosity, pore size and interconnectivity, were crucial to translating in vitro-engineered cell-scaffold constructs into bone tissues 5,6,[18][19] . One of the main challenges in bone tissue engineering was to develop scaffolds with optimal mechanical properties, biocompatibility, and architecture for cell colonization and organization -the latter being key to ensuring the integration of a scaffold with bone tissue.…”
Section: Discussionmentioning
confidence: 99%
“…The most popular are natural scaffolds composed from collagen or hyaluronic acid seeded with autologous chondrocytes to treat the cartilage defects (Kim et al 2011). PGA, PLLA and PLGA have been evaluated in vitro and in vivo for cartilage tissue regeneration (Moran et al 2003, El Sayed et al 2013, Sato et al 2004. Among many studies, very promising results have been observed by Agrawal et al (Agrawal et al 2013).…”
Section: Cartilage Regenerationmentioning
confidence: 99%